A20 deficiency in myeloid cells deteriorates the onset of vitiligo in mice. Issue 3 (11th March 2021) - Li, He; Wang, Congpin; Li, Xiaoqing; Kong, Yinghui; Sun, Weiguo
Abstract: Melanocyte‐specific CD8 + T cells enrichment correlates with the severity of vitiligo, and the role of A20 derived from myeloid cells in the enrichment of pathogenic T cells is unknown. Premelanosome (PMEL)‐specific transgenic CD8 + T cells were adoptive transferred into Krt14‐Kitl* mice to construct the vitiligo model, which was further mated with A20 MKO mice and IKK2 fl/fl mice. Bone marrow cells were stimulated with 30% L929 cell‐conditioned medium, Fc‐human tumor necrosis factor, and lipopolysaccharides to induce bone marrow‐derived macrophages (BMDMs). The relative expression of CCL2, CCL5, and IL12A was detected with real‐time PCR, and nuclear factor kappa B (NFκB) related molecules were detected with Western blots. Fluorescence‐activated cell sorting (FACS) was utilized to assay the percent of innate and adaptive immune cells in the spleen and bone marrow, and CD45 + T in the skin. Down‐regulated A20 was detected in the skin biopsies of vitiligo patients. A20 deficiency did not affect the development of T cells, B cells, macrophages, and neutrophils. A20 negatively regulated the induction of proinflammatory chemokines (CCL2, CCL5, and IL12A) and NFκB‐related molecule expression in BMDMs, which could be blocked by NFκB knockout. It further revealed that A20 negatively regulated the onset of vitiligo in mice with diminished CD45 + cells enrichment, which could also be reversed by NFκB knockout. A20 deficiency in myeloid cells could deteriorate the onset of vitiligo in mice, and A20 can be considered as a treatment target.